INTERNAL THREATS TO ECONOMIC SECURITY OF THE EURASIAN ECONOMIC UNION - Ganeeva, M.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2017)
The relevance of the study is due to the fact that the Eurasian Economic Union in the modern global economy is the second economic union in the history of the development and existence of integration processes. It is one of the largest regional markets, which unites about 182.7 million people, it possesses the fifth part of the world’s gas reserves and 15% for oil, with total GDP of about 2.5 trillion dollars (about 85% of GDP in all CIS countries), the industrial potential of 600 billion dollars and the volume of agricultural production - 112 billion dollars, etc. Thus, the potential of the new integration association is unique. The question today is whether the five countries will be able to find common ground in their general economic interests to preserve the association and its further development, as well as through the accession of new post-Soviet countries. The Eurasian Economic Union can potentially become one of the most important subjects of the world economy, a regional and even a global leader, if the association secures its economic safety, or put in other words will ensure the positive economic effect for each member country. The purpose of this article is to identify internal threats to the economic security of EAEU. The study showed that the most important internal threats to economic security are: the differentiation of the economic development of member countries; preservation of raw material export model of the development in Russia and Kazakhstan; virtually no trade and investment cooperation between such pairs of countries as Belarus - Armenia, Kazakhstan - Armenia, Kyrgyzstan - Armenia, Belarus - Kyrgyzstan, Kazakhstan - Belarus; aggravation of member countries financial problems; discrepancy in transport infrastructure development to the current needs of the integration association; absence of a single payment system; absence of a system of general integration of economic interests, divergence of the member countries interests up to the opposite position. Taking into account the material analyzed and the results obtained, the conclusion was drawn on the need to develop mechanisms for neutralizing these threats.